Polypyrrole-multi walled carbon nanotube hybrid material supported Pt NPs for hydrogen evolution from the hydrolysis of MeAB at mild conditions - Karatas, Yasar (Sci Rep, 2019)
Herein, we report a facile method for the preparation of polypyrrole-multi walled carbon nanotube hybrid material including Pt nanoparticles (Pt@PPy-MWCNT NPs) and the use in methylamine borane (MeAB) for hydrolysis reaction at mild conditions. The prepared catalyst of Pt@PPy-MWCNT NPs was characterized by some advanced analytical methods. The catalytic experiments showed the Pt@PPy-MWCNT NPs can catalyze MeAB in aquatic solution with high catalytical performance at mild conditions. The reaction rate of catalytic hydrolysis with Pt@PPy-MWCNT NPs was found to be -d[CH(3)NH(2)BH(3)]/dt = + d[H(2)]/3dt = k(obs)[Pt@PPy-MWCNT](1.19) [MeAB](0.88). The TOF value for the hydrolysis of MeAB catalyzed with Pt@PPy-MWCNT NPs was detected to be 10234.2 1/h (170.57 1/min) which is very high compared with TOF values found for other catalysts. Enthalpy, entropy and activation energy for the hydrolysis of MeAB were calculated to be 31.57 kJ mol(−1), −119.97 J mol(−1) K and 34.27 kJ mol(−1), respectively.